2012
DOI: 10.1039/c2cc31320k
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Friedel–Crafts reactions in water catalyzed by a human telomeric G-quadruplex DNA metalloenzyme

Abstract: A human telomeric G-quadruplex (G4DNA) metalloenzyme, assembled with G4DNA and Cu(2+) ions, can catalyze the enantioselective Friedel-Crafts (F-C) reaction in water with good enantioselectivity (up to 75% ee). Furthermore, we found that the absolute configuration and the enantioselectivity of the product largely depend on the conformation and the sequence of G4DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 44 publications
2
71
0
Order By: Relevance
“…4 In addition, the Li group 5 found that double-stranded DNA from herring sperm is capable of catalyzing the dithioacetalization in water for a variety of aldehydes under mild reaction conditions. Recently, G-quadruplex DNA has been demonstrated as a promising catalyst for enantioselective Diels–Alder 68 and Friedel–Crafts 9 reactions.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, the Li group 5 found that double-stranded DNA from herring sperm is capable of catalyzing the dithioacetalization in water for a variety of aldehydes under mild reaction conditions. Recently, G-quadruplex DNA has been demonstrated as a promising catalyst for enantioselective Diels–Alder 68 and Friedel–Crafts 9 reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, under molecular crowding conditions, ODN-1-4 all displayed parallel conformations ( Figure S3 a-d). Although the reactions catalyzed by the DNA-Cu 2+ complex of ODN-1-4 all produce the opposite enantiomer of product 3 a, the enantioselectivities vary with different loop sequences (Table 4, entries [5][6][7][8]. These observations suggest that the loop sequence plays a crucial role in Table S4).…”
mentioning
confidence: 99%
“…[4] Very recently, a G4DNA metalloenzyme composed of G4DNA and copper(II) ions has been reported to be able to catalyze an enantioselective Friedel-Crafts reaction. [5] This biology/chemistry interface is an attractive area of research and awaits further extensive exploration. Herein, we report an enantioselective D-A reaction achieved through the use of human telomeric G4DNA-based catalysts.…”
mentioning
confidence: 99%
“…[5] This biology/chemistry interface is an attractive area of research and awaits further extensive exploration. Herein, we report an enantioselective D-A reaction achieved through the use of human telomeric G4DNA-based catalysts.…”
mentioning
confidence: 99%